Cultural intelligence in the 21st century: Su adaptación al mundo empresarial - Hernández Correa, Emilio; Tamargo Niebla, Mario (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The growth experienced by intercultural contacts in the last decades generates numerous challenges in different areas of personal and professional life. Cultural intelligence is progressively consolidating as the best tool to face them. It is an ability that combines the study of cultures from the psychological, geographical, historical, anthropological and sociological points of view. In order to analyse how to work on this capacity, an approach is proposed that is related to the business world. This paper presents the main solutions currently adopted to offer services related to the aforementioned capability.